SAUL BELLOW’S NOVEL: MAN’ SQUEST FOR SELFHOOD - Rameshwar Prasad chaudhari (International Journal of Multidisciplinary Research and Studies, 2021)
Dangling Man was Saul Bellow’s first novel, and it was published in 1944. At the time of its release, it was hailed as "one of the most honest pieces of testimony on the psychology of a whole generation who have grown up during the war," and it was considered to be one of the best works of literature at the time. 78, authored by Edmund Wilson Bellow, in the novel, is regarded to have caught both the prevalent worry that is growing out of the societal disorder and the torturing impact that this upheaval is having on an individual’s sense of selfhood. This reflects Wilson’s remark, which can be seen throughout the novel. It would appear that Bellow has taken the unpredictability, anxiety, and dread that are prevalent in society and implanted them into the psyche of Joseph, who is the protagonist of the story. The plot of the book seems to revolve around Joseph’s eventual victory over the lawlessness of the world, which is intent on eradicating his sense of who he is. As a result, the book might be seen as Joseph’s search for his sense of self within the context of a type of spiritual barrenness that he and the world around him share.